O último trem para Alexandria - Bevilacqua, Luiz (Estudos Avançados, 2019)
The industrial revolution, which began supported by the scientific development of the 18th century, introduced changes in the social structure around the world. Craftsmen were dismissed and industrial production moved to large manufacturing complexes. Countries that were not able to adopt the new structure of production or to prioritize knowledge and creativity were dominated and subjected to a socio-economic dependency that continues to this day. Nowadays, we are plunged in a “cultural revolution” supported by extraordinary ongoing technological advances. Several universities will be discontinued; large transnational centers of scientific and cultural production will be set up; university professors, the craftsmen of our times, will be dismissed; and learning will have to resort to the information network installed on the planet. We are about to be swallowed up by the new revolution. There are ways out, but we need courage, daring and hard work in a network of national cooperation.